An Analysis on the Moisture and Thermal Protective Performance of Firefighter Clothing Based on Different Layer Combinations and Effect of Washing on Heat Protection and Vapour Transfer Performance - Ozgur Atalay; Senem Kursun Bahadir; Fatma Kalaoglu (Advances in Materials Science and Engineering)
Fabric assemblies for firefighting clothing have been tested for heat protection and comfort. The constituent materials and fabric structures have been specifically selected and tailored for firefighters’ clothing. In order to do this, four types of outer shell fabrics, four types of moisture barrier fabrics, and four types of heat barriers with different weights and material compositions were used to make a multilayered fabric assembly. Heat transfer (flame), heat transfer (radiant), and water vapour resistance tests were conducted according to the latest EN469 test standard which also recommends washing tests. These tests reveal that material content and material brand have considerable effect on the required performance levels of heat protection. In addition, while washing tests have improved water vapor transfer properties, they have a deteriorating effect on heat protection performance. Considering heat protection and moisture comfort properties, the optimal assemblies are thereby identified.